Synthesis and biological evaluation of heterocyclic bis-aryl amides as novel Src homology 2 domain containing protein tyrosine phosphatase-2 (SHP2) inhibitors. Issue 11 (1st June 2020) - Satheeshkumar, Rajendran; Zhu, Rui; Feng, Bo; Huang, Chao; Gao, Ya; Gao, Li-Xin; Shen, Chao; Hou, Ting-Jun; Xu, Lei; Li, Jia; Zhu, Yun-Long; Zhou, Yu-Bo; et al.
Graphical abstract: Abstract: The Src homology-2 domain containing protein tyrosine phosphatase-2 (SHP2) is a convergent node for oncogenic cell-signaling cascades including the PD-L1/PD-1 pathway. Consequently, SHP2 has emerged as a compelling target for novel anti-cancer agents. Replacing one of phenyl ring in PTP1B inhibitor 1 with heterocyclic ring led to a series of heterocyclic bis-aryl amide derivatives. The representative compound 7b displayed SHP2 inhibitory activity with IC50 of 2.63 ± 0.08 μM, exhibited about 4-fold selectivity for SHP2 over TCPTP and had no detectable activity against SHP1 and PTP1B. These preliminary results could provide a possible opportunity for the development of novel SHP2 inhibitors with optimal potency and improved pharmacological properties.